Structural and Electrical Characteristics of Metal-Ferroelectric Pb1.1(Zr0.40Ti0.60)O3-Insulator (ZnO)-Silicon Capacitors for Nonvolatile Applications - S. R. Krishnamoorthi; K. S. Venkatesh; Rajangam Ilangovan (Advances in Condensed Matter Physics)
In this work metal-ferroelectric-insulator-semiconductor (MFIS) thin-film structures using Pb1.1Zr0.40Ti0.60O3 (PZT) as the ferroelectric layer and zinc oxide (ZnO) as the insulator layer were fabricated on n-type (100) Si substrate. Pb1.1Zr0.40Ti0.60O3 and ZnO thin films were prepared on Si by the sol-gel route and thermal deposition method, respectively. On the optimized PZT (140 nm) and ZnO (40 nm) films were examined by scanning electron microscope (SEM). From AFM data the root mean square (r.m.s.) roughness of the film surface is 13.11 nm. The leakage current density of ZnO/n-Si (MIS) structure was as low as 1.8 × 10−8 A/cm2 at 2.5 V. The capacitance versus voltage (C-V) characteristics of the annealed ZnO/Si (MIS) diode indicated the good interface properties and no hysteresis was observed. Au/PZT (140 nm)/ZnO (40 nm)/Si (100) leakage-current density was about 5.7 × 10−8 A/cm2 at positive bias voltage of 3 V. The large memory window width in C-V (capacitance-voltage) curve of Au/PZT/ZnO/Si capacitor was about 2.9 V under ±12 V which thus possibly enables nonvolatile applications. The memory window as a function of temperature was also discussed.